Galiana: història d’un falcó. - FERRAGUD, CARMEL; OLMOS DE LEÓN, RICARDO M.; BATALLER, VICENT (Scripta, 2021)
In 1365 a lawsuit between the noblemen Berenguer of Galiana and Bernat Togores took place before the Court of the governor of Mallorca about the property of a falcon. Bernat Llemosí, a trainer of birds of prey, found himself involved in the case. The witnesses presented to clarify the facts provided really valuable information, and partly unknown, about the practice of this hunting art in the context of the Balearic Islands and Western Europe. A complete edition of the document is presented and thoroughly analysed in this study.